Military Customs and Traditions / Militêre Gewoontes en Tradisies - Militaria, Edotorial Team (Scientia Militaria - South African Journal of Military Studies, 2012)
Origins of the retreat ceremony While the Retreat Ceremony itself is one of the few uniquely South African military traditions, it derives from the old British military custom of ’beating the Retreat’ (by drum) which originated in the sixteenth century. In its original form the custom has been variously interpreted as a signal to literally ’retreat’ at the end of a day’s fighting, or as a means of summoning those soldiers required to stand the night’s watch. By the eighteenth century, however, a contemporary British Treatise On Military Discipline explicitly defined the practice thus: